WADAH AKTIFITAS KREATIF DI MARUNDA, JAKARTA UTARA - Syamil Mumtaz; Diah Anggraini (Jurusan Arsitektur dan Perencanaan, 2020)
Marunda North Jakarta is known as a fisherman settlement area that has been aged for hundreds of years, besides that this area is also the location of low-income housing construction for Low-Income Community Groups (MBR) whose residents are residents who are relocated from various villages in Jakarta, so that the residents of the flat are very heterogeneous. The diverse backgrounds of the Marunda people cause differences in culture and daily habits that create the creation of social boundaries that result in a lack of harmony in the social sphere between residents of Rusunawa and Kampung Nelayan communities, in the process of relocating some residents to lose their jobs. Apart from that, the difference in the shape of the dwellings that were different from those previously densely landed and now are now vertical which causes the formation of spatial boundaries that did not exist before. There is a need that can support the community to create harmony in the diversity of the Marunda community in social, economic and cultural aspects. This study aims to develop a Marunda Activity Center design concept as a third place to accommodate the activities of Marunda residents using the Transprogramming method. The building is designed by combining programs that are spatially different, with the aim of producing programs that are fit to the community so that they can build social interaction and can support the economy to improve the quality of life which will have an impact on the welfare of the people of Marunda. AbstrakMarunda Jakarta Utara dikenal sebagai kawasan pemukiman nelayan yang telah berusia ratusan tahun. Selain itu kawasan ini juga merupakan lokasi dibangunnya rusunawa bagi kelompok Masyarakat Berpenghasilan Rendah (MBR) yang sebagian penduduknya adalah warga yang direlokasi dari berbagai kampung di Jakarta, sehingga penghuni rusun bersifat sangat heterogen. Beragamnya latar belakang warga Marunda menyebabkan terjadinya perbedaan dalam budaya dan kebiasaan sehari-hari yang menjadikan terciptanya batas sosial yang mengakibatkan kurangnya keharmonisan dalam lingkup sosial baik antar penghuni Rusunawa maupun masyarakat Kampung Nelayan. Dalam proses relokasi sebagian warga kehilangan pekerjaannya. Selain hal tersebut perbedaan bentuk tempat tinggal yang berbeda dari yang sebelumnya padat landed lalu sekarang menjadi vertikal yang menyebkan terbentuknya batas spasial yang sebelumnya tidak ada. Terdapat kebutuhan yang dapat menunjang masyarakat untuk mewujudkan keharmonisan dalam keberagaman masyarakat Marunda pada aspek sosial, ekonomi dan seni budaya. Kajian ini bertujuan untuk menyusun suatu konsep perancangan Marunda Activity Center sebagai third place untuk mewadahi kegiatan warga Marunda dengan menggunakan metode Transprogramming. Bangunan dirancang dengan menggabungkan program-program yang berbeda secara spasialnya, dengan tujuan untuk menghasilkan program yang fit kepada masyarakat sehingga dapat membangun interaksi sosial dan dapat menunjang perekonomian untuk meningkatkan kualitas hidup yang akan berdampak pada kesejahteraan masyarakat Marunda.